Gatekeepers to Success: Missouri’s Exclusionary Approach to School Discipline - Christie B. Carrino (Washington University Journal of Law & Policy, 2016)
This Note first traces the history of the Federal Government’s involvement in education and moves into a discussion of the history of state and local control of education. Carrino uses the context of Missouri law to describe the policy implications of different disciplinary schemes and Missouri’s interaction with these policies. Carrino concludes with an argument for the implementation of a ballot measure in Missouri to better align state discipline statutes with the spirit of the Missouri Constitution and its educational guarantees.
Keywords: education; Missouri; disciplinary schemes; United States Department of Education; school to prison pipeline